EVALUATION OF DAIRY MANAGEMENT IN PROPERTIES OF THE QUINTA DO SOL AND PEABIRU: A MULTI-CASE STUDY - CAMARGO, G.; BÁNKUTI, F.I.; BUSTOS MAC LEAN, P.A (Revista Brasileira de Engenharia de Biossistemas, 2013)
The objective of the current study was to evaluate the management in dairy farms by comparing them with the management described in bibliographies. This evaluation was done using questionnaires for 10 producers in the regions of Quinta do Sol and Peabiru. The questionnaires were elaborated according to the analysis of the main necessities and critical points for a good performance in the dairy production. It was concluded that the use of individual records for animals expedite the handling, and therefore helps to prevent and solve problems that may occur. In the results, it was observed that most producers do properly feeding management, however only 20% make use of individual records, this also occurs in reproductive management. Although in production and health management systems, it was observed that most of the producers does not use proper handling and also does not make use of individual records. In assessing the management in dairy farms and comparing them with the management recommended in bibliographies, it was observed that the producers partially performs the appropriate and designed management for a good milk production.